Modeling Moral Behavior Based on Parent-Child Interaction and Perceived Social Support: The Mediation Role of Cultural Intelligence and Religious Orientation in Female High School Students - Zahra Naji; Fatemeh Khoeini; Hasan Asadzadeh; Ali Jalili Shishvan (Iranian Journal of Educational Research)
Objective: This investigation was undertaken with the objective of constructing a model of moral behavior predicated on the interactions between parents and children, alongside perceived social support, with cultural intelligence and religious orientation serving as mediating variables among high school females in Tehran. Methods: The research employed a descriptive correlational methodology. The statistical population for this study encompasses all female high school students aged between 12 and 16 years, with a total of 400 individuals selected as a sample through the application of cluster sampling during the academic year of 2023. Data collection was facilitated through the utilization of standardized questionnaires. Results: The findings indicated that parent-child interactions exert a direct influence on moral behavior; additionally, it was determined that perceived social support similarly has a direct impact on moral conduct. Further results corroborated that parent-child interactions do not influence moral behavior via the mediating function of cultural intelligence. Ultimately, additional findings revealed that perceived social support exerts an indirect effect on ethical behavior through the mediating influence of cultural intelligence. Conclusions: The results predominantly validate the significance of social support, familial context, and parental influence in both mitigating and enhancing moral behavior.